2002
DOI: 10.1111/j.1741-3737.2002.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Parental Acceptance‐Rejection and Psychological Adjustment: A Meta‐Analysis of Cross‐Cultural and Intracultural Studies

Abstract: ࡗ Perceived Parental Acceptance-Rejection and Psychological Adjustment: A Meta-Analysis of Cross- Cultural and Intracultural StudiesMeta-analytic procedures were used to pool information from 43 studies worldwide to test one of the major postulates of parental acceptancerejection theory (PARTheory). Specifically, using child and adult versions of the Parental Acceptance-Rejection Questionnaire (PARQ) and the Personality Assessment Questionnaire (PAQ), these studies allowed us to assess the claim within PARTheo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

28
264
2
25

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(319 citation statements)
references
References 25 publications
(12 reference statements)
28
264
2
25
Order By: Relevance
“…Accordingly, the most basic needs of children are the care, comfort, support and love that will be provided by their parents. The whole humanity has this need, regardless of culture, race, physical characteristics, social status, language, geography and the other similar restrictive conditions (Khaleque & Rohner, 2002). Rohner's (2004) definition of parental acceptance and rejection form the warmth dimension of parenting.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the most basic needs of children are the care, comfort, support and love that will be provided by their parents. The whole humanity has this need, regardless of culture, race, physical characteristics, social status, language, geography and the other similar restrictive conditions (Khaleque & Rohner, 2002). Rohner's (2004) definition of parental acceptance and rejection form the warmth dimension of parenting.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, WUSCT was found to be translated into the Arabic language by other scholars and was used cross-culturally in other languages, i.e. has been used on people from different cultures [11,12,13,14].…”
Section: Instrumentsmentioning
confidence: 99%
“…According to the personality subscale of PARTheory, adult's emotional safety and wellbeing are affected by the perceived acceptance and rejection by their parents in childhood (6). PARTheory suggested that in cases of rejection, the people are located at the negative end of the, hostility, abuse, negative selfesteem, negative self-adequacy, emotional unresponsiveness, emotional instability and negative worldview (12).…”
Section: Introductionmentioning
confidence: 99%